2015
DOI: 10.1515/commun-2015-0013
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in recall and liking of arousing television commercials

Abstract: This article examines whether there are differences between older and younger adults in recall and liking of arousing television commercials. As hypothesized, the experiment demonstrated that older adults remembered brands and products in calm commercials better than in arousing commercials, and they also liked calm commercials more. In contrast, younger adults remembered brands and products in arousing commercials better and they liked these commercials more. In addition, (curvi)linear relationships showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
(96 reference statements)
0
5
0
Order By: Relevance
“…A neuroimaging study by Dolcos, Katsumi, and Dixon (2014) showed increased activity in the anterior cingulate cortex and decreased activity in the amygdala in older versus younger adults in response to low-, but not high-, arousal negative images, suggesting that older adults selectively dampen responses to low-arousal negative stimuli. Last, in a marketing study, van der Groot, van Reijmersdal, and Kleemans (2015) demonstrated that older adults preferred calm television advertisements with few camera changes, slower speech, and relaxing or no music over arousing advertisements, and also had better memory for the products featured in the calm advertisements. Thus, making informed decisions while bombarded with high-arousal appeals from fraudsters, regardless of their valence, may be particularly unsettling for older adults.…”
Section: Older Adults' Processing Of Emotionally-arousing Informationmentioning
confidence: 99%
“…A neuroimaging study by Dolcos, Katsumi, and Dixon (2014) showed increased activity in the anterior cingulate cortex and decreased activity in the amygdala in older versus younger adults in response to low-, but not high-, arousal negative images, suggesting that older adults selectively dampen responses to low-arousal negative stimuli. Last, in a marketing study, van der Groot, van Reijmersdal, and Kleemans (2015) demonstrated that older adults preferred calm television advertisements with few camera changes, slower speech, and relaxing or no music over arousing advertisements, and also had better memory for the products featured in the calm advertisements. Thus, making informed decisions while bombarded with high-arousal appeals from fraudsters, regardless of their valence, may be particularly unsettling for older adults.…”
Section: Older Adults' Processing Of Emotionally-arousing Informationmentioning
confidence: 99%
“…The strength and vulnerability integration (SAVI) model 22 posits that this diminished physiological flexibility hinders the effective regulation of high arousal in older adults, leading to more aversive response to high-arousal stimuli as they age. Thus, attentional and memory processing can be particularly compromised for high-arousal stimuli in older age 23 26 . For instance, Goot et al found that high level of arousal in advertisement stimuli associated with worse memory retention for older adults, but not for younger adults 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, attentional and memory processing can be particularly compromised for high-arousal stimuli in older age 23 26 . For instance, Goot et al found that high level of arousal in advertisement stimuli associated with worse memory retention for older adults, but not for younger adults 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Potentially, older adults remember less from television commercials than younger adults because of the audiovisual production features of commercials regardless of the type of content, thus 'overriding' the positive effect of emotional content. Future research is called for to test this explanation, and to delve into the question of how such production features differentially affect older and younger adults' processing of advertising (Van der Goot et al, 2015).…”
Section: Conclusion and Discussionmentioning
confidence: 99%